Ion-Exchange Resin Anticoagulation (I-ERA): A Novel Extracorporeal Technique for Regional Anticoagulation. Issue 3 (September 2016) - Zanella, Alberto; Scaravilli, Vittorio; Castagna, Luigi; Giani, Marco; Magni, Federico; Laratta, Matteo; Rezoagli, Emanuele; Ferrari, Chiara; Mazzola, Silvia; Albertini, Mariangela; Pesenti, Antonio
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Extracorporeal treatments always require blood anticoagulation. We tested feasibility and efficacy of a novel technique for regional extracorporeal blood anticoagulation based on calcium removal by ion-exchange resins (i-ER), called ion-exchange resin anticoagulation (i-ERA). Methods: Eight swine were connected to a veno-venous extracorporeal circuit comprising a hemodiafilter and an i-ER. Blood flow was 150 mL/min. Hemodiafiltrate was generated at 975 mL/min and passed through the i-ER. A fraction of the calcium-free hemodiafiltrate was returned to the hemodiafilter (675 mL/min), while the remaining was recirculated prior the hemodiafilter (300 mL/min) to dilute blood entering the hemodiafilter. A calcium replacement solution was continuously infused. Two hours after i-ERA start, blood was sampled from inlet, before the hemodiafilter (prehemodiafilter blood) and from outlet of the extracorporeal circuit for ionized calcium (iCa) concentration and thromboelastography (TEG). Arterial blood was collected for blood gas analyses, electrolytes concentrations, and plasma free hemoglobin. Hemodynamics and ventilation were monitored. Results: i-ERA reduced iCa from 1.28 ± 0.05 mmol/L (inlet) to 0.47 ± 0.03 mmol/L (prehemodiafilter blood) and 0.25 ± 0.03 mmol/L (outlet). Prehemodiafilter blood and outlet samples showed no sign of clot formation (reaction time ( R ) >60 min; maximal amplitude (MA) = 0 (0-0) mm), while blood-inlet had normal coagulation ( R = 8.5 (5.8–10.2) min; MA = 65.2 (63.2–68.7) mm). Arterial gas analyses and electrolytes concentrations, hemodynamics, and ventilation were unchanged. No hemolysis was recorded. Conclusions: In a swine model, i-ERA proved feasible and effective in reducing iCa and preventing clot formation with TEG analyses. Further studies are warranted to evaluate the long-term efficacy and safety of i-ERA. Level of Evidence: V-therapeutic animal experiment.